Epigenetic Modifications in Acute Myeloid Leukemia: Prognosis, Treatment, and Heterogeneity - Goldman, Samantha L.; Hassan, Ciaran; Khunte, Mihir; Soldatenko, Arielle; Jong, Yunji; Afshinnekoo, Ebrahim; Mason, Christopher E. (Frontiers in Genetics, 2019)
Leukemia, specifically acute myeloid leukemia (AML), is a common malignancy that can be differentiated into multiple subtypes based on leukemogenic history and etiology. Although genetic aberrations, particularly cytogenetic abnormalities and mutations in known oncogenes, play an integral role in AML development, epigenetic processes have been shown as a significant and sometimes independent dynamic in AML pathophysiology. Here, we summarize how tumors evolve and describe AML through an epigenetic lens, including discussions on recent discoveries that includes prognostics from epialleles, changes in RNA function for hematopoietic stem cells and the epitranscriptome, and novel epigenetic treatment options. We further describe the limitations of treatment in the context of the high degree of heterogeneity that characterizes acute myeloid leukemia.